Local community: Memajukan perekonomian melalui ekonomi kreatif - Ma’rifatunnisa, Ma’rifatunnisa (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of local communities in promoting the economy through the creative economy. The creative economy has become one of the important strategies for economic development in various countries. This article aims to examine the role of local communities in advancing the economy through creative economic development. This article shows that local communities play an important role in advancing the economy through the creative economy by providing a platform for creativity, facilitating knowledge exchange, and building collaborative networks. Local communities also contribute to improving the skills of their members, promoting local products, and encouraging the sustainability of the creative economy. However, challenges such as limited resources and lack of government support still need to be overcome to maximize the potential of the creative economy in the region.